Multimorbidity characteristics in older adults and their associated factors in complex networks: a cross-sectional study - Wu, Dan; Xu, Jiani; Zhang, Haibo; Zhang, Kai; Zhu, Yongqian (Frontiers in Public Health, 2025)
BackgroundMultimorbidity of chronic diseases has become an increasingly serious public health problem. However, the research on the current situation of multimorbidity in the older adults in Jiangsu, China is relatively lacking.MethodsWe surveyed a total of 229,926 inpatients aged above 60 and with two or more chronic diseases in the First Affiliated Hospital with Nanjing Medical University from January 1, 2015 to December 31, 2021. The Apriori algorithm was used to analyze the association rules of the multimorbidity patterns in old adults.ResultsThe mean age of these patients was 72.0 ± 8.7 years, and the male-to-female ratio was 1: 1.53. These patients during the COVID-19 period (from 2020 to 2021) displayed younger, higher male rate, shorter median length of hospital stay, higher ≥6 multimorbidities rate and lower median cost than those not during the COVID-19 period (from 2015 to 2019). In all of these patients, the top 5 chronic diseases were “Hypertensive diseases (I10-I15),” “Other forms of heart disease (I30-I52),” “Diabetes mellitus (E10-E14),” “ischaemic heart diseases (I20-I25)” and “Cerebrovascular diseases (I60-I69).” The complex networks of multimorbidity showed that Hypertensive diseases had a higher probability of co-occurrence with multiple diseases in all these patients, followed by diabetes mellitus, other forms of heart disease, and ischaemic heart diseases (I20-I25).ConclusionIn conclusion, the patterns of multimorbidity among the aged varied by COVID-19. Our results highlighted the importance of control of hypertensive diseases, diabetes, and heart disease in most periods. However, during the pandemic period, we should pay more attention to diseases that require urgent treatment, such as malignant tumors. For different periods, the spectrum of diseases we focus on should change accordingly.